Answer:
The standard form of y = 3 x + 1 is -3x + y = 1 .
The standard form of y = 4x - 7 is -4x + y = -7.
Step-by-step explanation:
Here the given equation are:
y = 3 x + 1
and y = 4x - 7
The above equations are of the form: y = m x + C
Now, the STANDARD FORM of the equation is Ax + By = C
<u>Consider equation 1: </u>
y = 3 x + 1
or, y - 3x = 1
or. -3x + y = 1
⇒ The equation -3x + y = 1 is in STANDARD FORM.
<u>Consider equation 2: </u>
y = 4 x - 7
or, y - 4x = -7
or. -4x + y = -7
⇒ The equation -4x + y = -7 is in STANDARD FORM.
Step-by-step explanation:
no sn as. kojsshsusishheidhsusjjsbsbshsbsjs7ehsjsnkosvsjsishshshsjdjjddyfygyvrcudjdhdudhsjsudhdjs
Step-by-step explanation:
it is 12 because 12 - 7 is 5 the number 4 is the number multiplied by 3
Answer:
35
Step-by-step explanation:
x=35
y=7
There is no solution so C.